Extra nodal NK/T cell lymphoma, nasal type: atypical presentation of Rhinosinusitis cannot be missed! - Che' Man, Mohamad; MZ, Abdul Zaki Ar Rasyid; Paul, Mark; D, Intan Nurjannah (Universiti Kuala Lumpur, 2024)
Extra nodal NK/T cell lymphoma (ENKTCL) nasal type is an Epstein Barr virus (EBV)-associated lymphoma of NK cells or T cells, predominantly involving extra nodal tissue. It most commonly affects the upper aerodigestive tract, including the nasal cavity, nasopharynx, paranasal sinuses, and palate. We report a case of a 50-year-old man with a blocked right nasal passage associated with unilateral right facial pain and swelling extending down to the neck. Endoscopic and radiological examinations revealed the presence of a soft tissue lesion within the right nasal cavity. Histopathological examination confirmed the diagnosis of ENKTCL nasal type.